Un detall autobiogràfic del rei Jaume el Conquistador: la devoció a santa Maria de València. - FERRANDO FRANCÉS, ANTONI (Scripta)
There is an episode in the Llibre dels feits of King James the Conqueror where he declares his devotion to Saint Mary of Valencia. It is an autobiographical detail that has been questioned by some scholars. The article analyzes and confirms the textual transmission of that mention, which has had a reflection in the historical tradition of the Cathedral of Valencia.